Stories from ancient Canaan - Coogan, Michael David (Philadelphia : The Westminster Press, 1978)
Contents: Introduction. __Aqhat.___The healers.___Kirta.___Baal
Includes bibliographical references
Keywords: Ugaritic literature -- Translations into English; English literature -- Translations from Ugaritic